Role of Signaling Transduction Pathways in Development of Castration-Resistant Prostate Cancer - Takahiro Inoue; Osamu Ogawa (Prostate Cancer)
Almost all patients who succumb to prostate cancer die of metastatic castration-resistant disease. Although docetaxel is the standard treatment for this disease and is associated with modest prolongation of survival, there is an urgent need for novel treatments for castration-resistant prostate cancer (CRPC). Great advances in our understanding of the biological and molecular mechanisms of prostate cancer progression have resulted in many clinical trials of numerous targeted therapies. In this paper, we review mechanisms of CRPC development, with particular focus on recent advances in the understanding of specific intracellular signaling pathways participating in the proliferation of CRPC cells.